Ethical culture and emotional intelligence in students of the IV and VI cycle of primary education EIB of the Monseñor Elías Olázar Public Pedagogical Higher Education School in the year 2024 - Vasquez Arevalo, Gretty (2025)
The objective of this research was to determine the relationship between ethical culture and emotional intelligence in students of the Monseñor Elías Olázar School of Pedagogical Public Higher Education in the year 2024. With this aim, current sources were investigated, leading to the constitution of a systematic theoretical framework that allowed us to delve into the understanding of the relationship between the variables. A quantitative approach, with a correlational and non-experimental design, was used with a representative sample of students from the institution. Validated questionnaires were applied to measure both variables and the Spearman evaluation was used to analyze the relationship between them. The results showed a significant positive assessment between ethical culture and emotional intelligence, with a coefficient of 0.725 and a significance level less than 0.001. It will be observed that students with greater development in ethical values also had a greater capacity for self-awareness, self-regulation, motivation, empathy and social skills, fundamental dimensions of emotional intelligence.